Scenarios of public policies adopted by the national biodiesel production program in Brazil - Maintinguer, Sandra Imaculada [UNESP]; Antoniosi, Luciana; Ribeiro, Marla Lucia; Ferrante, Vera Lucia Silveira Botta (Univ Tecnologica Fed Parana-utfpr, 2022)
Brazil is among the four largest biodiesel producers. Several challenges need to be overcome, since economic activities of this kind require regular production, technical skills and effective public policies that boost representativeness to the domestic and foreign markets. This study evaluated the public policies of the National Biodiesel Production Program (PNPB), with an emphasis on the Social Fuel Seal (SCS), aiming to deepen knowledge with the productive, regulatory and governmental sector, for its improvement of production and integration of family farming. Relevant barriers and perspectives have been identified. It is necessary to invest in the construction of new public policies and regulations with incentives from the State, in addition to the participation of the entire biodiesel production chain, which meet the needs of the entire segment.
Keywords: Biofuel; Diesel; Regulatory framework; Family farming